2017
DOI: 10.12659/msm.898297
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Transcription Factors Associated with Lung Squamous Cell Carcinoma

Abstract: BackgroundLung squamous cell carcinoma (lung SCC) is a common type of lung cancer, but its mechanism of pathogenesis is unclear. The aim of this study was to identify key transcription factors in lung SCC and elucidate its mechanism.Material/MethodsSix published microarray datasets of lung SCC were downloaded from Gene Expression Omnibus (GEO) for integrated bioinformatics analysis. Significance analysis of microarrays was used to identify differentially expressed genes (DEGs) between lung SCC and normal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
(40 reference statements)
1
21
0
Order By: Relevance
“…More recent studies revealed that the DNA-binding capability of RDM1 is enhanced at low pH, indicating that it may function in acidic conditions such as the tumor microenvironment (17). Furthermore, RDM1 has been shown to be upregulated at the mRNA level in lung squamous cell carcinoma (18). Nonetheless, despite the growing evidence, the precise function of RDM1 in NSCLC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies revealed that the DNA-binding capability of RDM1 is enhanced at low pH, indicating that it may function in acidic conditions such as the tumor microenvironment (17). Furthermore, RDM1 has been shown to be upregulated at the mRNA level in lung squamous cell carcinoma (18). Nonetheless, despite the growing evidence, the precise function of RDM1 in NSCLC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…SCLC is another more aggressive form of LC, and the 5-year overall survival of SCLC patients is only about 5% [ 3 6 ]. With advances in pathologic and molecular studies of LC, early detection, diagnosis, and treatment are of great significance for the management of LC [ 7 , 8 ]. Hence, identification of molecules that are correlated with the clinical features of LC patients might be helpful in the management of LC.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the polymorphism of P73 is suggested to be highly associated with susceptibility to smoking‐related lung cancer . Moreover, transcription factors (TFs) have been identified in lung SCC . In spite of these findings, lung cancer prognosis in clinical practice has not improved.…”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, transcription factors (TFs) have been identified in lung SCC. 7 In spite of these findings, lung cancer prognosis in clinical practice has not improved. Currently, there are no identified molecular targets for therapy of smoking-related lung cancer.…”
Section: Introductionmentioning
confidence: 99%